Population and Civil Registration Public Services Digital Transformation During the Covid-19 Pandemic - Ria Angin; Putri Robiatul Adawiyah (Universitas Muhammadiyah Tangerang, 2023)
This article's main focus research result is on the unpredictable public service in Covid-19 pandemic as a factor in the quick digitization of public services. During the Covid-19 Pandemic, in the Population and Civil Registry Office of Situbondo Regency adopted an online population management service information system (SILAO). Data for this study were gathered through observation and interviews using a qualitative methodology. Using qualitative descriptive analysis is applied to data collection and analysis. Face-to-face interaction has been displaced with electronic delivery of public services. The results of the study show that This article's main focus is on the unpredictable COVID-19 pandemic as a factor in the quick digitization of public services. During the Covid-19 Pandemic, the Population and Civil Registry Office of Situbondo Regency adopted an online population management service information system (SILAO). Face-to-face interaction has been displaced with electronic delivery of public services. This research found that the public service technology system that had been built during the pandemic did not always guarantee that the public service had been implemented successfully. Public service technology system, requires a stable internet signal. The power of the internet, which has been unstable, has affected the poor quality of public services.Â Fokus utama artikel Â ini adalah pada ketidakpastian Â pelayanan publik di masa pandemi Covid-19 sebagai faktor cepatnya digitalisasi pelayanan publik. Pada Masa Pandemi Covid-19, di Dinas Kependudukan dan Catatan Sipil Kabupaten Situbondo mengadopsi sistem informasi pelayanan pengelolaan kependudukan secara daring (SILAO). Data untuk penelitian ini dikumpulkan melalui observasi dan wawancara dengan menggunakan metodologi kualitatif. Menggunakan analisis deskriptif kualitatif diterapkan pada pengumpulan dan analisis data. Interaksi tatap muka telah digantikan dengan penyampaian layanan publik secara elektronik. Hasil penelitian menunjukkan bahwa fokus utama artikel ini adalah pada pandemi COVID-19 yang tidak dapat diprediksi sebagai faktor dalam digitalisasi layanan publik yang cepat. Pada Masa Pandemi Covid-19, Dinas Kependudukan dan Catatan Sipil Kabupaten Situbondo mengadopsi sistem informasi pelayanan pengelolaan kependudukan secara online (SILAO). Interaksi tatap muka telah digantikan dengan penyampaian layanan publik secara elektronik. Penelitian ini menemukan bahwa sistem teknologi pelayanan publik yang telah dibangun selama pandemi tidak selalu menjamin bahwa pelayanan publik telah berhasil dilaksanakan. Sistem teknologi pelayanan publik, membutuhkan sinyal internet yang stabil. Kekuatan internet, yang selama ini tidak stabil, telah mempengaruhi buruknya kualitas pelayanan publik.